Effects of Schematic Factors on the EFL Reading Comprehension - Wido H. Toendan (Universitas Negeri Malang, 2016)
This paper report an experimental study on the effects of EFL reading proficiency (PROF), text structure (TEXT), and prefactory Framework (PREF) on the EFL reading comprehension (COMP) of expository texts. The subjects of the study were the intermediate and advanced readers of the English Department students of STKIP Unika Widya Mandala Surabaya. Results of the study significantly reveal the independent effects of EFL PROF, TEXT, and PREF on the COMP of expository texts. Based on the findings of the study, some suggestions intended for the reading instructors, developers of the written instructional materials, and area of further research are offered